Long-term follow-up of large maxillary advancements with distraction osteogenesis in growing and non-growing cleft lip and palate patients. Issue 1 (January 2015) - Meazzini, Maria Costanza; Basile, Valentina; Mazzoleni, Fabio; Bozzetti, Alberto; Brusati, Roberto
Summary Background Maxillary distraction osteogenesis (DO) in cleft lip and palate patients has been described by several authors, but most studies have a relatively short follow-up and do not clearly separate growing patients from non-growing patients. Method The records of 22 consecutive patients affected by cleft lip and palate, who underwent Le Fort I osteotomy and maxillary distraction with a rigid external distractor (RED), were reviewed. The sample was subdivided into a growing and a non-growing group. All patients had pre-DO cephalometric records, immediately post DO, 12 months post DO and long-term records with a long-term follow-up of >5 years (range 5–13 years). As a control sample for the growing group, cleft children with a negative overjet not subjected to distraction or any protraction treatment during growth were followed up until the completion of growth. Results The average maxillary advancement in the growing group was 22.2 ± 5.5 mm (range: 15–32 mm); in the non-growing group, it was 17.7 ± 6.6 mm (range: 6–25 mm). Excellent post-surgical stability was recorded in the adult sample. On the other hand, growing children had an average 16% relapse in the first year post DO and an additional 26% relapse in the long-term follow-up. Conclusions This study seems to point out that early Le Fort I DO allows for the correction of very severe deformities. It is followed by a relatively high amount of true skeletal relapse in children with cleft lip and palate. Prognosis should be discussed in depth with the family and true aesthetic and psychological needs assessed.